Launch vehicle systems engineering life‐cycle evolution and comparison. Issue 4 (19th March 2019) - Gibson, Denton
Abstract: Historically, through extensive government involvement, most orbital rocket companies have adopted the government's systems engineering approach. However, over the past decade, the Federal government has been less involved in the development of new launch vehicles. The diminishing involvement by the Federal government has given way to the rise of nontraditional systems engineering life‐cycle approaches for launch vehicle development. This paper explores the advantages and disadvantages of the different system engineering life‐cycle approaches in the launch vehicle industry.